2017
DOI: 10.1002/er.3755
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the environmental, economic, and material developments of the solar and wind sources coupled with the energy storage systems

Abstract: Summary There is a constant growth in energy consumption and consequently energy generation around the world. During the recent decades, renewable energy sources took heed of scientists and policy makers as a remedy for substituting traditional sources. Wind and photovoltaic (PV) are the least reliable sources because of their dependence on wind speed and irradiance and therefore their intermittent nature. Energy storage systems are usually coupled with these sources to increase the reliability of the hybrid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 93 publications
0
40
0
Order By: Relevance
“…Therefore, production of electrical energy is an important area of study for many researchers. Some of the most popular and environmentally friendly energy sources to produce electric energy are renewable energy sources such as solar energy and wind energy . Although these sources have great potential for sustainable energy supply, production of electricity in any time depends on its sources.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, production of electrical energy is an important area of study for many researchers. Some of the most popular and environmentally friendly energy sources to produce electric energy are renewable energy sources such as solar energy and wind energy . Although these sources have great potential for sustainable energy supply, production of electricity in any time depends on its sources.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can be seen from the results of density of state (DOS) that Co(C 6 H 5 CO 2 ) 2 (C 5 H 5 N) 2 has high stability. From the Figure 1B, Co-3d states show much stronger hybridization with N-2p states and O-2p states from −6 to 3 eV, and it can be also observed that N-2p states and O-2p states overlap in the vicinity of the Fermi level, which can also enhance the stability of Co(C 6 H 5 CO 2 ) 2 (C 5 H 5 N) 2 .…”
Section: Methodsmentioning
confidence: 88%
“…Therefore, we first determined the adsorption of O 2 by testing different adsorption sites and adsorption modes. There are following possible surface active adsorption sites for O 2 6) ). All possible adsorption sites of O 2 and ORR intermediates on Co(C 6 H 5 CO 2 ) 2 (C 5 H 5 N) 2 were examined, and the most stable adsorption configurations and the corresponding adsorption energies were depicted in Figure 2 and Table 2.…”
Section: Adsorption Of O 2 and Orr Intermediatesmentioning
confidence: 99%
“…1 However, renewable power generation, such as wind and PV power generation, will cause great disturbance to the power grid if connected to the grid directly, since it has the disadvantage of fluctuation and intermittence. 6,7 Pumped hydro storage (PHS) is a preferable storage device, with low cycle cost, and is considered the most mature technology. 4,5 Many storage devices have been applied in hybrid systems.…”
Section: Introductionmentioning
confidence: 99%